Penerapan Metode Casework dalam Membangun Rasa Kepercayaan Diri Residen Residivis - Ulina Tassia Br Hutagaol; Randa Putra Kasea Sinaga (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
One of the providers of social welfare services is residents or former fostered social institutions, especially for one of the recidivist residents. The social stigma attached to recidivist residents causes shame and low self-esteem which aggravates the emotional state so planning is needed in dealing with these problems. Through the practice of fieldwork as a social worker, it aims to help improve the social functioning of a recidivist resident in the uncertainty of acceptance when returning to society. Using the casework method with several stages, namely (1) Engagement, Intake, Contract, (2) Assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination which shows better development in building client morale